Sikap Keuangan dan Pengaruhnya terhadap Perilaku Keuangan Gen Z di Surabaya: Peran Literasi Keuangan dan Fintech - Waninghiyun, Vidya Hangialevi; Haryati, Tantina (Universitas Negeri Padang, 2025)
Purpose –This study aims to examine the role of financial attitudes as a personal psychological factor that is evaluative, affective, or instrumental in explaining the financial behavior of Generation Z. Furthermore, this study considers financial literacy and fintech as variables influencing financial behavior.Design/methodology/approach –The study was conducted using a quantitative approach by distributing questionnaires to Generation Z in Surabaya. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to test the relationships between variables in the research model.Findings –The results indicate that financial attitudes have a significant influence on Gen Z's financial behavior. Financial literacy and fintech use also contribute to shaping more targeted financial behavior.Originality/value – This study makes an empirical contribution by highlighting the psychological role of financial attitudes in the financial behavior model of Generation Z and combining them with financial literacy and fintech variables within a research framework based on the Theory of Planned Behavior (TPB).Research limitations/implications –The limitations of this study lie in the use of a cross-sectional design and the limited geographical coverage of respondents. The study findings can serve as a basis for academics, policymakers, and fintech service providers to design strategies to improve the financial behavior of the younger generation.Keywords: Financial attitudes, financial behavior, generation z, financial literacy, fintech.Article Type: Research Paper